Introduction to NJWLS 2021-4 - Buch, Anders (Nordic Journal of Working Life Studies, 2021)
This issue of Nordic Journal of Working Life Studies makes six new research articles available. The first article of the issue is written by Marit Lensjø: Grounded Theory Analysis of Work-based TVET and Intersectional Challenges Between Constriction Workers. It explores the Norwegian technical vocational education and training (TVET) model that combines school-based education with work-based apprenticeship in authorized enterprises (...)